Bentuk-Bentuk Perubahan Pertukaran dalam Perkawinan Bajapuik - M, Maihasni; Sumarti, Titik; Sri Wahyuni, Ekawati (Sodality: Jurnal Sosiologi Pedesaan, 2010)
The objective of this paper to identified and analysis of types that use in bajapuik marriage as a basic of exchange and factors that its influence. The reseach is a qualitative aproach with using multi method approaches in order to explain the phenomena proposed.The result of the study showed that types exchange in bajapuik marriage involved; 1) uang jemputan; 2) uang hilang; 3) uang selo; 4) uang tungkatan. All of types that are exchenged in bajapuik marriage in this moment. In general, the types emerge are caused effect economy and spesific education and inhabitant mobility.